New directions for special collections : an anthology of practice - Thomas, Lynne M.; Whittaker, Beth M. (Santa Barbara, California : Libraries Unlimited, 2017)
Special collections today from rare books and other specialized book collections to audio recordings and visual images offer librarians limitless opportunities to showcase their skills in curating, preserving, and offering access to these resources to patrons. Drawing on innovative practices and enduring values to address challenges and opportunities in the broad realm of special collections librarianship, this book updates the notion of special collections to the wide range of materials, institutions, and contexts where they exist today. The contributed essays describe the various kinds of innovative projects and practices that are sought by IMLS and other funding agencies today and serve to illustrate how going beyond a traditionally limited idea of special collections opens doors to far more engaging opportunities. Spanning the converging worlds of academic and special libraries, rare book collections, archives, museums, and other cultural heritage institutions, this book will be useful to newcomers and seasoned professionals alike. The essays address the recurring themes of managing and welcoming change and the impact of digital technologies throughout the book, whether regarding new approaches to outreach and instruction, the acquisition and curation of non-traditional collections, new structures for discovery and access in a digital world, or the nature of special collections work now. Both experienced professionals and recent graduates from one of the booming archival studies programs will find this text invaluable in creating a successful career in special collections or cultural heritage curation today and in the near future.
Includes bibliographical references and index.
oif 17/12/2019
Loans
Keywords: Libraries--Special collections; Special libraries--Administration; Archives--Administration; Special librarians; Archivists